Immunity Response of Gumboro and ND Vaccination Result which Given with Time Spacing in Broiler Chicken - Yuwono, Endro; Setyawati, SJA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
An experiment was planed to knowÂ the possibility of negative effect on Gumboro vaccination program. This program has a possibility to cause âSickâ condition on fabrious bursal of broiler chicken. From that case, it need time spacing for subsequent vaccination program, for instance ND vaccination program.Â Time spacing is very importance to broiler chicken for recovering that âSickâ condition because of Gumboro vaccination effect. The purpose of his research was to know the best time spacing between Gumboro and ND vaccination program on broiler chicken. An experimentalÂ method was used in this research, and the material used was 216 broiler chickens. A 3x4 factorial arrangement (Gumboro vaccination as factor A and ND vaccinationÂ as factor B) with three broiler chickens per unit and six replicates of each treatment combination was used in theÂ research. Variables tested ofÂ this experiment HI ND antibody titer, body weightÂ of 4 weeks old, and the symptom appeared after vaccination program. Anava was used to analyze the data obtained and used orthogonal polynomial for subsequent analysis. The researchÂ results showed that the best time spacing was eight days and there was no symptomÂ appeared after Â GumboroÂ vaccination program. There were no significantly influence of vaccination treatments on broiler chicken health and body weight. (Animal Production 3(2): 67-73 (2001)Â Key Words: Vaccination, symptom, antibody